IMPROVING STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT OF FIRST GRADE STUDENTS AT MTs. DDI KEL. BARU TOLITOLI THROUGH PICTURE - Diyenti Rusdin (Universitas Madako Tolitoli, 2019)
The objective of this research is to find out whether the application of picture effective to improve students’ ability in writing descriptive text. It is a pre-experimental research. The study is the first grade of MTs. DDI Kel. Baru Tolitoli. It is conduct class (VII A). The data are obtain through a pre-test and post-test. The writer use SPSS 16.0 program to analyze the data collection. The result of the analysis show that the application of picture contribute greatly to the students in writing descriptive text. The mean score of pre-test is 65.70 while in the post-test improve up to 79.46. Moreover, the Minimum Mastery Criterion of English lesson is 75 (seventy-five). Then the data of both test are analyze by using T-test, and the result show that the T-count value is 10.839 greater than T-table value is 2.045. It can be inferred that the application of picture is very effective to improve students’ ability in writing descriptive text. Key words: picture, writing, descriptive text.